2002
DOI: 10.1007/bf02345075
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory effects of internal jugular vein compression: A computer simulation study

Abstract: The effects of compression of the internal jugular veins and the inferior vena cava are simulated using an equivalent electronic circuit, which included simulation of cardiocirculatory phenomena and special features of the cerebral circulation. Compression of the inferior vena cava resulted in a profound decrease in cardiac output (from 4.5 to 1.51min(-1)) and arterial pressure (from 140/85 to 50/35 mmHg). Compression of the internal jugular veins resulted in a negligible decrease in cardiac output and arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…So far, mathematical studies of the cranial system have addressed issues such as the coupling between the CSF and the vascular compartment, CSF production and absorption, cerebral autoregulation and the transient behaviour of the CSF system (MARMAROU et al, 1978;SCHMIDT et al, 1997;TAKEMAE et al, 1987;URSINO, 1988a;URSINO and DI GIMMARCO, 1991;URSINO et al, 1995;BOSNJAK and KORDAS, 2002). However, the non-linear nature of the venous system is usually either ignored or addressed indirectly by the parameters of the venous circulation being forced to match the experimental observations in a limited range of PcsF.…”
Section: Da Vcsr CC ---(1) Dpcsfmentioning
confidence: 97%
“…So far, mathematical studies of the cranial system have addressed issues such as the coupling between the CSF and the vascular compartment, CSF production and absorption, cerebral autoregulation and the transient behaviour of the CSF system (MARMAROU et al, 1978;SCHMIDT et al, 1997;TAKEMAE et al, 1987;URSINO, 1988a;URSINO and DI GIMMARCO, 1991;URSINO et al, 1995;BOSNJAK and KORDAS, 2002). However, the non-linear nature of the venous system is usually either ignored or addressed indirectly by the parameters of the venous circulation being forced to match the experimental observations in a limited range of PcsF.…”
Section: Da Vcsr CC ---(1) Dpcsfmentioning
confidence: 97%
“…Because the adult brain is surrounded by the inflexible cranial bones, if arterial flow remains constant but venous flow decreases acutely, blood will accumulate in the capillary system to induce brain swelling, leading to cerebral venous hypertension. One study showed that compression of the internal jugular vein, increasing its pressure from 5 to 10 mm Hg, raises intracranial pressure (ICP) from 9 to 22 mm Hg and cerebrospinal fluid volume from 120 to 145 mL [4]. Elevated cerebral venous pressure subsequently decreases cerebral blood flow and increases ICP, leading to pressure-dependent blood brain barrier disruption [5].…”
Section: Commentmentioning
confidence: 99%
“…[3][4][5] IJV compression and engorgement of the cranial venous system enlarges the brain and increases brain turgor (makes stiffer) through changes in vascular dynamics and cerebrospinal fluid (CSF) absorption. 3,[6][7][8][9][10][11] This reduces relative motion, or slosh, between the brain and the skull and diminishes deformation of the brain. Two previous animal studies have shown a striking reduction in axonal injury through pre-injury application of a customized cervical collar introducing IJV compression.…”
Section: Introductionmentioning
confidence: 97%